An integrated approach to develop professional and technical skills for Informatics Engineering students - Fernandes, João M. (2012)
Many of the current approaches used to teaching and learning in engineering education are not the most appropriate to prepare students for the challenges they will face in their professional careers. The active involvement of students in their learning process facilitates the development of the technical and professional competencies they need as professionals. This article describes the organisation and impact of a mini-conference and project work - the creation of a software product and its introduction in the market - aimed at the development of professional competencies in general and writing skills in particular. The course was evaluated by assessing the students’ perception of the development of a number of professional competencies through a questionnaire completed by 125 students of two consecutive editions. The results indicate that the project work and the mini-conference had a positive impact on students’ perceptions of the development of professional competencies.